Acceptance, Indications and Chances of Focal Therapy in Localized Prostate Cancer: A Real-World Perspective of Urologists in Germany - Wenzel, Mike; Borgmann, Hendrik; Hardenberg, Jost von; Cash, Hannes; Welte, Maria N.; Bründl, Johannes; Hoffmann, Manuela A.; Höfner, Thomas; Borkowetz, Angelika (Journal of endourology, 2021)
Purpose: Focal therapy (FT) became a frequently discussed treatment strategy of localized prostate cancer (PCa), but the acceptance and evaluation of FT by practicing urologists are still unclear. - Methods: A 25-item anonymized online questionnaire (SurveyMonkey®) was compiled by the German Society of Residents in Urology Academics Prostate Cancer Working Group and sent to the members of the German association of Urology. Logistic regression analysis was performed to determine parameters for suggestion FT. - Results: Two hundred ten urologists (median age 49 years) participated, from which 72% stated PCa as their main treatment focus. Ninety-nine percent of urologists were aware of and 54% wanted to improve their knowledge about FT. Sixty-five percent do not treat PCa with FT. FT is seen as an alternative to active surveillance and radiotherapy/radical prostatectomy by 66% and 37%, respectively. Regarding FT treatment strategies, 35% and 45% would treat all or all significant PCa foci, respectively, whereas 19% would treat mainly the index foci. Currently, 27% believe that FT will be an option as standard treatment in future, but 48% would not suggest FT to their patients, owing to an absence of evidence and insufficient diagnostic tools for proper patient selection today. Suggesting FT to patients is associated with self-performing FT (odds ratio [OR] 2.88, 95% confidence interval [CI] 1.31-6.31) and believing in FT as a standard treatment in future (OR 9.05, 95% CI 6.68-22.30) (both p < 0.01). - Conclusion: FT has currently no wide acceptance in German practicing urologists, mainly attributable to an absence of evidence for FT superiority compared to standard treatments.
Gesehen am 21.08.2024